2019
DOI: 10.1186/s13023-019-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementing reflective multicriteria decision analysis (MCDA) to assess orphan drugs value in the Catalan Health Service (CatSalut)

Abstract: Background Orphan medicines show some characteristics that hinder the evaluation of their clinical added value. The often low level of evidence available for orphan drugs, together with a high budget impact and an incremental cost-effectiveness ratio many times higher than drugs used for non-orphan diseases, represent challenges in their appraisal and effective access to clinical use. In order to explore how to handle these hurdles, the Catalan Health Service (CatSalut) began an initiative on a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 9 publications
2
57
0
Order By: Relevance
“…The pros and cons of each weighting method have been extensively discussed elsewhere and should be judged not only on their level of precision but also on their theoretical foundations 31,36,37 . Although not comparable, the criteria used in our research have some resemblances with the research by Guarga et al (2019) 30 . Our approach allows for more granularity at criteria hierarchy and the results we obtained showed substantial differences in the ranking of the criteria relative to Guarga et al (2019) 30 .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The pros and cons of each weighting method have been extensively discussed elsewhere and should be judged not only on their level of precision but also on their theoretical foundations 31,36,37 . Although not comparable, the criteria used in our research have some resemblances with the research by Guarga et al (2019) 30 . Our approach allows for more granularity at criteria hierarchy and the results we obtained showed substantial differences in the ranking of the criteria relative to Guarga et al (2019) 30 .…”
Section: Discussionsupporting
confidence: 73%
“…(2016) organized a twelve criteria MCDA framework into three categories: health technology characteristics (five criteria), indicated disorder characteristics (two criteria), and public health aspects (five criteria) 29 . More recently, Guarga et al (2019) suggested a reflective MCDA to assess the value OMPs in the Catalan Health Service (CatSalut) composed by 10 quantitative and 4 qualitative criteria, respectively; disease severity, unmet needs, improvement of efficacy/effectiveness, improvement of safety/tolerability, improvement of patient perceived health/PRO, type of therapeutic benefit, annual patient cost of treatment, other medical costs, quality of evidence, expert consensus/clinical practice guidelines; population priorities and access (principle of equity), common goal and specific interests, system capacity and appropriate use of OMPs, opportunity costs and affordability (budget impact) 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGNSS was subsequently taken over by the Highly Specialized Technologies (HST) group for NICE, who also use the MCDA approach (48). In Spain, the Spanish Agency for Medicines and Health Products developed a MCDA framework based on the EVIDEM framework (49) and similarly in Catalonia (50). The region of Lombardia in Italy has adopted a MCDA approach to regulate the introduction of new health technologies.…”
mentioning
confidence: 99%
“…While ample research has been performed in recent years on the suitable criteria for inclusion in a MCDA model for orphan drugs (42,50,53), less research seems to have been done on the weights or preferences that should be applied to the different criteria. The weighting scales used in research range from 5-point scales (50,54), to 10-point scales (55) and several studies mention using a 100-point scale (34,41,56). A pilot study by Reddy et al included a group of eight participants (plus the facilitator) to select the criteria that should be considered for a MCDA framework for several public health preventative programmes.…”
mentioning
confidence: 99%